2020
DOI: 10.3389/fmicb.2020.587556
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Stable Hydrogen-Driven Microbiome in a Highly Radioactive Storage Facility on the Sellafield Site

Abstract: The use of nuclear power has been a significant part of the United Kingdom’s energy portfolio with the Sellafield site being used for power production and more recently reprocessing and decommissioning of spent nuclear fuel activities. Before being reprocessed, spent nuclear fuel is stored in water ponds with significant levels of background radioactivity and in high alkalinity (to minimize fuel corrosion). Despite these challenging conditions, the presence of microbial communities has been detected. To gain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 135 publications
0
7
0
Order By: Relevance
“…Efforts to determine the microbial community in biofilms could provide useful information about whether there are other organisms that might be useful for bioremediation of radionuclide-containing waters and other applications, as well as add to current understanding of biofouling problems in inhospitable nuclear environments. A range of other indoor SNFPs have been studied more recently ( Rivasseau et al, 2013 ; Tišáková et al, 2013 ; Karley et al, 2017 ; Bagwell et al, 2018 ; Ruiz-Lopez et al, 2020 ), and in some cases have been shown to host stable microbial communities over extended periods of time, as was observed in an indoor SNFP on the Sellafield site that was dominated by the hydrogen-metabolising genus Hydrogenophaga ( Ruiz-Lopez et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Efforts to determine the microbial community in biofilms could provide useful information about whether there are other organisms that might be useful for bioremediation of radionuclide-containing waters and other applications, as well as add to current understanding of biofouling problems in inhospitable nuclear environments. A range of other indoor SNFPs have been studied more recently ( Rivasseau et al, 2013 ; Tišáková et al, 2013 ; Karley et al, 2017 ; Bagwell et al, 2018 ; Ruiz-Lopez et al, 2020 ), and in some cases have been shown to host stable microbial communities over extended periods of time, as was observed in an indoor SNFP on the Sellafield site that was dominated by the hydrogen-metabolising genus Hydrogenophaga ( Ruiz-Lopez et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, it plays an important role in water purification and the carbon cycle. Moreover, the Sediminibacterium genus was found to be one of the dominant bacteria in the storage pool of radioactive materials [ 52 ], and the reclaimed water was treated with a low concentration of chlorine [ 53 ], signifying its oxidation resistance. However, the dominant bacteria were replaced by the Acidovorax genus when the reclaimed water was treated with ultraviolet and chlorine together [ 54 ], indicating that ultraviolet light had adverse effects on the Sediminibacterium genus.…”
Section: Resultsmentioning
confidence: 99%
“…The Caulobacter strain OR37 isolated from subsurface sediments at Oak Ridge (USA) was proven to be tolerant to 200 μM of uranium at pH 7 ( Utturkar et al, 2013 ). The genus Caulobacter has been identified in spent nuclear fuel storage pools in Sellafield (UK) ( Foster et al, 2020 ; Ruiz-Lopez et al, 2020 ). Caulobacter bacteria are well known for their distinctive ability to live in low-nutrient environments ( Hu et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%